PENGEMBANGAN WEBSITE PROFIL PERUSAHAAN BERBASIS WORDPRESS CMS SEBAGAI MEDIA PROMOSI DI PT AMD ACADEMY INDONESIA - Priantoni, Sean; Rochman, Fatkhur (Transpublika Publisher, 2025)
An effective online presence enhances a company's image and broadens its audience. PT AMD Academy Indonesia Malang, a human resource training institution, requires an optimized promotional platform. This study aims to develop, assess quality, and evaluate the effectiveness of a company website as a promotional tool. Using the R&D (Research & Development) method with a waterfall model, the process included analysis, design, implementation, testing, and maintenance. The website was designed with user needs in mind, incorporating wireframes, UI/UX elements, and optimized content. Testing confirmed its responsiveness, usability, and information quality. Results indicate the website is highly effective as a promotional medium, enhancing the company’s visibility and engagement in the training sector. Further development is recommended to align with the company’s growth.